ESG criteria adoption by financial institutions: an investigation on lending impact - Dalla Riva, Enrico (2023)
The adoption of environmental, social, and governance (ESG) standards by financial institutions can be a powerful accelerator for sustainable development, however it is necessary to determine why financial institutions do or do not accept such criteria. We draw on the coercive, normative, and mimetic forces identified by DiMaggio and Powell (1983) and Scott (1995, 2003) in institutional theory and on social capital theory, which discusses the role of social ties of firms to people and communities (Coleman, 1988, Nahapiet & Ghoshal, 1998), to seek answers to the question of how the phenomenon of sustainable finance operates in the loan market. This research used a mixed method investigation to explore the use of ESG criteria in the financial system which primarily evolved from a quantitative analysis using difference-in-difference regressions on data on new loans from the database of the financial regulators and was complemented by a qualitative approach that started with focus group sessions with experts and ended with a content analysis of the reports in conjunction with interviews with financial institution officers. This strategy was used to answer the following questions: What are the motivators for ESG implementation in financial institutions? How have these changes been incorporated into the risk assessment processes of financial institutions? What is the impact of ESG regulations on the loan market in Brazil? Although the regulator’s efforts regarding socio-environmental risks have been recognised since 2014, the impact on the real economy remains unknown. The results show that institutional forces are associated with organisational change towards ESG business integration, but without major economic impact. Furthermore, based on social capital theory, the study confirmed heterogeneities within the financial system, particularly in the operations of credit unions, where maturities appear to be influenced by legislation, although such an endeavour has not yet been systematically applied to all loan terms (i.e., portfolio volumes and interest rates), nor has it considered the high climate risks of the financial sector. This research contributes to finance and sustainability pieces of literature when both institutional and social capital theories are employed to explain the sustainable finance phenomena within financial institutions progressing in such an interdisciplinary field. Additionally, it offers a regulatory impact study for future uses.